A network of phosphatidylinositol 4,5-bisphosphate binding sites regulates gating of the Ca(2+)-activated Cl(−) channel ANO1 (TMEM16A) - Yu, Kuai (Proc Natl Acad Sci U S A, 2019)
ANO1 (TMEM16A) is a Ca(2+)-activated Cl(−) channel that regulates diverse cellular functions including fluid secretion, neuronal excitability, and smooth muscle contraction. ANO1 is activated by elevation of cytosolic Ca(2+) and modulated by phosphatidylinositol 4,5-bisphosphate [PI(4,5)P(2)]. Here, we describe a closely concerted experimental and computational study, including electrophysiology, mutagenesis, functional assays, and extended sampling of lipid–protein interactions with molecular dynamics (MD) to characterize PI(4,5)P(2) binding modes and sites on ANO1. ANO1 currents in excised inside-out patches activated by 270 nM Ca(2+) at +100 mV are increased by exogenous PI(4,5)P(2) with an EC(50) = 1.24 µM. The effect of PI(4,5)P(2) is dependent on membrane voltage and Ca(2+) and is explained by a stabilization of the ANO1 Ca(2+)-bound open state. Unbiased atomistic MD simulations with 1.4 mol% PI(4,5)P(2) in a phosphatidylcholine bilayer identified 8 binding sites with significant probability of binding PI(4,5)P(2). Three of these sites captured 85% of all ANO1–PI(4,5)P(2) interactions. Mutagenesis of basic amino acids near the membrane–cytosol interface found 3 regions of ANO1 critical for PI(4,5)P(2) regulation that correspond to the same 3 sites identified by MD. PI(4,5)P(2) is stabilized by hydrogen bonding between amino acid side chains and phosphate/hydroxyl groups on PI(4,5)P(2). Binding of PI(4,5)P(2) alters the position of the cytoplasmic extension of TM6, which plays a crucial role in ANO1 channel gating, and increases the accessibility of the inner vestibule to Cl(−) ions. We propose a model consisting of a network of 3 PI(4,5)P(2) binding sites at the cytoplasmic face of the membrane allosterically regulating ANO1 channel gating.